2011
DOI: 10.1007/s10549-011-1554-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating lymphocytes are correlated with response to neoadjuvant chemotherapy in triple-negative breast cancer

Abstract: The purpose of the present study was to identify histological surrogate predictive markers of pathological complete response (pCR) to neoadjuvant chemotherapy (NAC) in triple-negative breast cancer (TNBC). Among 474 patients who received NAC and subsequent surgical therapy for stage II-III invasive breast carcinoma between 1999 and 2007, 102 (22%) had TNBC, and 92 core needle biopsy (CNB) specimens obtained before NAC were available. As controls, CNB specimens from 42 tumors of the hormone receptor-negative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
214
3
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(236 citation statements)
references
References 35 publications
15
214
3
4
Order By: Relevance
“…A total of 480 studies were first identified for evaluation. Based on the criteria described in the methods, 19 publications were eligible for inclusion in the present meta-analysis (10,12,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). The bibliographies of these 19 publications were also searched, but this did not provide further studies for inclusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 480 studies were first identified for evaluation. Based on the criteria described in the methods, 19 publications were eligible for inclusion in the present meta-analysis (10,12,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). The bibliographies of these 19 publications were also searched, but this did not provide further studies for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 stu dies (10,(15)(16)(17)(18)(19)(20)24,25,(27)(28)(29)(30) reported the pCR rates in patients with TNBC and non-TNBC who received NAC. There was no heterogeneity between the results of different studies (I 2 =23%, P=0.21), so the fixed-effects model was applied for data analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of markers has been proposed to better predict outcome of neoadjuvant chemotherapy, reports on another 4 of these markers are published in this issue of the journal [10][11][12][13]. Therefore, some general prerequisites should be described for the development and validation of such new markers: preferably markers should be searched for separately in cohorts with either HR?/HER-, HER2?, or triple-negative tumors; new markers should be immediately validated on independent data sets before their release; and markers should not only be correlated with the occurrence of a pCR but also with survival.…”
mentioning
confidence: 99%
“…This issue also contains reports of novel predictive markers such as p53 mutation status, the extent tumor infiltrating lymphocyte and the cell death pathway mediator Serpin3 [16][17][18]. However, markers predictive of specific agents and regimens are needed for clinical decisionmaking and will require further evaluation in both neoadjuvant and adjuvant trials.…”
mentioning
confidence: 99%